2021
DOI: 10.1177/0044118x211044524
|View full text |Cite
|
Sign up to set email alerts
|

Swimming Against the Tide: Young Informal Traders’ Survival Strategies in a Competitive Business Environment in Zimbabwe

Abstract: Informal trading in the town of Bindura, Zimbabwe is a competitive venture just like in other parts of the world. The competitiveness is characterized by young traders aged 18 to 24 years being elbowed out by those established in the business, hence, the study sought to interrogate the experiences of young informal traders. Employing a qualitative research framework with an interpretive philosophical dimension, the study established that young informal traders deploy their agency to survive in such a harsh env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…An innovative mindset describes all the behaviour by which an individual can influence the innovation process, particularly focusing on behaviour oriented towards generating and applying ideas (De and Den, 2007). From the SMEs' perspective, it has been found that entrepreneurs with an innovative mindset will prioritise innovation as a tool to achieve business success and use strategic management practices and intellectual capital management as opposed to an SME owner-manager who lacks an IM (Voln a et al, 2015;Kabonga et al, 2021b). Women entrepreneurs must have an ICD, which is defined by Lai et al (2010) as the female entrepreneur's belief and motivation for increased innovation.…”
Section: Introductionmentioning
confidence: 99%
“…An innovative mindset describes all the behaviour by which an individual can influence the innovation process, particularly focusing on behaviour oriented towards generating and applying ideas (De and Den, 2007). From the SMEs' perspective, it has been found that entrepreneurs with an innovative mindset will prioritise innovation as a tool to achieve business success and use strategic management practices and intellectual capital management as opposed to an SME owner-manager who lacks an IM (Voln a et al, 2015;Kabonga et al, 2021b). Women entrepreneurs must have an ICD, which is defined by Lai et al (2010) as the female entrepreneur's belief and motivation for increased innovation.…”
Section: Introductionmentioning
confidence: 99%
“…, 2015; Meyer, 2018), ENV (Khan et al. , 2015; Kabonga et al ., 2021a, b, c; Goby & Erogul, 2011), PSYC (Loras & Vizcaíno, 2013; Laudano et al ., 2019; Eisenberger et al. , 2005; Khan et al.…”
Section: Results Discussionmentioning
confidence: 99%
“…Rather poverty and unemployment are the two major challenges in the present world economy, with 80% of the extreme poor living in rural areas (Campos, Villani, Davis, & Takagi, 2018). Globally, most of the poorest individuals in rural areas are females (Suttie et al ., 2018; Okeke-Uzodike, 2019; Kabonga, Zvokuomba, Nyagadza & Dube, 2021). It has also been revealed that females have fewer economic rights, and lower access to economic opportunities and resources, including land and credit facilities, causing them to remain economically inactive (Hayford & Kloke-Lesch, 2013).…”
Section: Introduction and Contextualizationmentioning
confidence: 99%
“…Furthermore, it was discovered that social entrepreneurial intent significantly positively influences social entrepreneurial action (Kabonga et al , 2021b). This result suggests that the higher the level of social entrepreneurial intent, the higher the level of social entrepreneurial action.…”
Section: Discussionmentioning
confidence: 99%